Aplikasi Penambahan Kunyit dan Multinutrien Blok Plus pada Pakan Kambing Jawarandu terhadap Infestasi Endoparasit dan Konsumsi Pakan: Application Of Turmic Addition And Multinutrient Block Plus On The Jawarandu Goat’s Diet Towards Endoparasit Infestations And Feed Consumption - Retno Iswarin Pujaningsih; Dian Wahyu Harjanti; Baginda Iskandar Moeda Tampubolon; Widianto Widianto; Ahmad Ahsan; Wening Suri Pawestri (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Goat management in rural areas is still commonly done traditionally with little regard for health factors. One factor is the presence of parasitic worms in the goat's digestive tract which causes disturbed growth. The research aims to evaluate the effect of the addition of turmeric and multinutrient block plus (MNBP) in eliminating endoparasites and increasing feed intake of Jawarandu goats. The material used was 12 male Jawarandu goats weighing an average of 20 kg. A completely randomized design was used in this study with 4 treatments and 3 replications. Treatment T0: basal ration + MNBP; T1: T0 + 1% turmeric; T2: T0 + 3% turmeric; T3: T0 + 5% turmeric. The parameters observed were feed intake, weight gain, number of endoparasites and total eggs per gram of feces. Data analysis using analysis of variance significance level of 5% to determine the effect of treatment. If there is a treatment effect, it is followed by Duncan's multiple range test. The results showed a decrease in the number of endoparasites. The best treatment to induce an antibody system is T2 treatment, namely the addition of turmeric with a level of 3%. Feed intake was not significantly increasing although improving body weight gain in T2 and T3. The conclusion of the study is that the administration of MNBP and turmeric with a level of 5% has not been able to eliminate all endoparasites until the 28th day. MNBP and turmeric are useful as natural antioxidants. Increased level of turmeric can increase weight gain and immune system of goats. Keyword: Multinutrient blocks, turmeric, Jawarandu goats, endoparasite, feed intake